Utilization of red cabbage (Brassica oleracea var. Capitata L.) anthocyanins as a sensor for nitrite detection in domestic wastewater - Rogo, Ben Haryan Adi; Natasya, Vika Aulia; Attamimi, Najwa Sabila; Muliawan, Sidiq; Laila, Farida (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Monitoring wastewater quality is increasingly essential for enhancing wastewater treatment procedures. Domestic wastewater, produced by residential and commercial operations, contains considerable organic, inorganic, and biological pollutants, including nitrite ions, which provide serious health hazards. This research develops a nitrite detection sensor utilizing anthocyanins derived from red cabbage (Brassica oleracea var. Capitata L.). The extraction utilized ultrasonic-assisted extraction (UAE) using a solvent combination of 96% ethanol, distilled water, and 80% acetic acid, resulting in the maximum anthocyanin content of 7.653 mg/g dry weight. The sensor's performance was assessed in terms of stability, selectivity, and sensitivity. The results demonstrated temperature stability at 30°C, with a retention rate of 98.92%, and selectivity for nitrite was verified in the presence of several possible interfering chemicals. Sensitivity tests indicated a detection threshold of 250 ppm for nitrite. The sensor exhibited a shelf life of 19 hours at ambient temperature (25°C) and 11 days at 5°C.